2021
DOI: 10.1111/1751-7915.13919
|View full text |Cite
|
Sign up to set email alerts
|

A single change in the aptamer of the Lactiplantibacillus plantarum rib operon riboswitch severely impairs its regulatory activity and leads to a vitamin B2‐ overproducing phenotype

Abstract: Manufacturing of probiotics and functional foods using lactic acid bacteria (LAB) that overproduce vitamin B 2 has gained growing interest due to ariboflavinosis problems affecting populations of both developing and affluent countries. Two isogenic Lactiplantibacillus plantarum strains, namely a riboflavin-producing parental strain (UFG9) and a roseoflavin-resistant strain (B2) that carries a mutation in the FMN-aptamer of the potential rib operon riboswitch, were analysed for production and intraand extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…These results were expected due to an inhibitory effect of the FMN, upon internalization, in the riboflavin biosynthesis, proceeding to a latter expression of the rib operon when levels of the effector are exhausted in the cells. However, as expected the presence of the FMN had no influence on riboflavin production by the three mutant strains, since increase of fluorescence due to the presence of flavins was observed from the beginning of the exponential growth phase, as we have previously observed for riboflavin-overproducing L. plantarum mutants also carrying point mutations located in its corresponding aptamer of the FMN riboswitch ( 45 ). Consequently, these results and the fact that no mutations were found in the rib operon encoding the enzymes involved in the riboflavin biosynthetic pathway, strongly suggest that the mutations in the FMN-riboswitch are responsible for the riboflavin-overproducing phenotype of the W. cibaria B2 strains.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…These results were expected due to an inhibitory effect of the FMN, upon internalization, in the riboflavin biosynthesis, proceeding to a latter expression of the rib operon when levels of the effector are exhausted in the cells. However, as expected the presence of the FMN had no influence on riboflavin production by the three mutant strains, since increase of fluorescence due to the presence of flavins was observed from the beginning of the exponential growth phase, as we have previously observed for riboflavin-overproducing L. plantarum mutants also carrying point mutations located in its corresponding aptamer of the FMN riboswitch ( 45 ). Consequently, these results and the fact that no mutations were found in the rib operon encoding the enzymes involved in the riboflavin biosynthetic pathway, strongly suggest that the mutations in the FMN-riboswitch are responsible for the riboflavin-overproducing phenotype of the W. cibaria B2 strains.…”
Section: Resultssupporting
confidence: 82%
“…The Dsr from LAB produce extracellularly dextran by hydrolysis of sucrose molecules coupled to the transfer of glucose to the nascent α-glucan polymer ( 16 ). Moreover, we have shown that riboflavin produced by W. cibaria BAL3C-5, BAL3C-7, and BAL3C-22, as is the case in other LAB ( 12 , 45 ), can be detected and quantified in culture supernatants ( 32 ). Therefore, after growing the six LAB for 23 h in RAMS, the content of dextran and riboflavin present in the culture supernatants was determined, and the final biomass estimated by measuring the OD 600 nm and by plating ( Table 2 ).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…To our knowledge, this is the first study describing an L. reuteri strain with a spontaneous riboflavin-overproducing phenotype. Besides the well-reported investigation and applications of overproducing L. plantarum strains (16,18,(52)(53)(54)(55)(56) only few other species of food-grade bacteria including L. lactis (50), Leuconostoc mesenteroides, Propionibacterium freudenreichii (43); Limosilactobacillus fermentum (57); Weissella cibaria, and Leuconostoc spp. (58) have been reported for the vitamin B2 bio-enrichment of fermented foods.…”
Section: Discussionmentioning
confidence: 99%